Comprehensive management of anterior cruciate ligament and medial meniscus tear in a young female: a case report - Bora, Manu; Hood, Mitesh M. (International Surgery Journal, 2024)
Anterior cruciate ligament (ACL) and medial meniscus (MM) tears are prevalent knee injuries, especially among young athletes, significantly impacting joint stability and function. This case study presents the clinical evaluation, diagnostic imaging, and surgical management of a 25-year-old female with a complete ACL tear and grade III medial meniscus tear. The patient's clinical presentation, including pain and instability following a sports injury, was corroborated by magnetic resonance imaging (MRI) findings, revealing the severity of her injuries. Arthroscopic surgery, involving ACL reconstruction and meniscus repair, was performed with successful postoperative recovery. This case underscores the critical role of detailed assessment and advanced imaging in diagnosing complex knee injuries, highlighting the efficacy of arthroscopic techniques in facilitating optimal recovery and restoring knee function.